Design, Fabrication, and Swimming Performance of a Free-Swimming Tuna-Mimetic Robot - Sayyed Farideddin Masoomi; Axel Haunholter; Dominic Merz; Stefanie Gutschmidt; XiaoQi Chen; Mathieu Sellier (Journal of Robotics)
High efficiency in cruising is a determining factor in developing tuna-mimetic robots. So far, a number of tuna-like robots have been made. Nevertheless, the University of Canterbury has developed its own tuna-like robot called UC-Ika 1 to investigate and to accordingly improve the swimming performance of the biomimetic swimming robots. In order to do so, the propulsion system of a tuna with respect to its thrust and resistive forces is studied. Following that, the fish robot is designed and fabricated considering the tuna propulsion system. The robot is then tested several times to investigate its swimming performance. Comparison of the speed and efficiency of UC-Ika 1 with those of other tuna-like robots shows a promising improvement of cruising performance of UC-Ika 1.